PERAN PSIKOLOGI INDUTRI DAN ORGANISASI DALAM MENINGKATKAN KESEJAHTERAAN KARYAWAN DAN PRODUKTIVITAS KERJA - Dwita Agustina Putri; Feby Nurhalizah Siregar; Rini Andriansi; Ramadhan Pasaribu; Said Agil Lubis (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2025)
This study aims to examine the contribution of PIO in improving employee welfare and work productivity. The method used is a literature review of 10 accredited national journals published in 2020–2025. The results of the study indicate that the application of PIO principles such as stress management training, effective communication, organizational support, and positive work culture can improve employee welfare. This welfare is an important link in increasing work productivity. The conclusion of this study confirms that the integration of PIO into HR policies is needed to encourage sustainable performance. It is recommended that organizations strengthen psychological support and implement welfare-based policies to achieve employee efficiency and loyalty.